First report of the whitesaddled catshark Scyliorhinus hesperius (Springer 1966) in Guatemala's Caribbean Sea. Issue 1 (December 2016) - Hacohen-Domené, Ana; Polanco-Vásquez, Francisco; Graham, Rachel
Abstract Background The present study represents the first record ofScyliorhinus hesperius in Guatemala's Caribbean Sea. Methods Five male whitesaddled catsharks, S. hesperius, were captured in 200 m deep waters of Guatemala's Caribbean coast. Results and Conclusion All specimens were male with total lengths ranging from 420 mm to 510 mm. These fish represent the first record of mature maleS. hesperius, the first record for this species in Guatemalan territorial waters, and a range extension in the Western Central Atlantic.